Cross sectional survey of perpetrators, victims, and witnesses of violence in Bogotá, Colombia. Issue 5 (1st May 2003) - Duque, L F; Klevens, J; Ramirez, C
Abstract : Objectives: To establish the prevalence and distribution of witnesses, victims, and perpetrators of different types of violence in the general population and the proportion of victims consulting health services or reporting the incident to authorities. Methods: Cross sectional survey of a random sample of 3007 inhabitants between the ages of 15 and 60 in the city of Bogotá, Colombia, in 1997, based on a face to face interview. Results: Age adjusted past year prevalence of witnesses, victims, and perpetrators of physical aggression was 61%, 27%, and 27%, respectively, while lifetime prevalence of witnesses, victims, and perpetrators of assault with a weapon in this population reached 70%, 55%, and 5.8%. Between 11% and 67% of the victims consulted a health service and less than 32% reported the incident to an authority. Those involved in most types of physical violence tended to be young, male, from lower middle social classes, with some degree of secondary education, and single or divorced. Conclusions: Prevalence of witnesses and victims of violence in this sample appears to be high, while perpetrators constitute a small proportion. Violence is not equally distributed throughout the population suggesting the possibility of identifying a population at higher risk for the development of intervention programmes.